2007
DOI: 10.1056/nejmoa060610
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus Surgical Drainage of the Pancreatic Duct in Chronic Pancreatitis

Abstract: Surgical drainage of the pancreatic duct was more effective than endoscopic treatment in patients with obstruction of the pancreatic duct due to chronic pancreatitis. (Current Controlled Trials number, ISRCTN04572410 [controlled-trials.com].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
475
2
39

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 758 publications
(542 citation statements)
references
References 34 publications
13
475
2
39
Order By: Relevance
“…Dite et al [5] , in a prospective randomized trial comparing endoscopic and surgical therapy for chronic, painful, obstructive pancreatitis, reported complete resolution of pain at the five-year follow-up in 37% of patients after surgery and in 14% of those after endotherapy; short-term results were similar in the two groups. Similar data have been recently published by Cahen et al [6] .…”
Section: Chronic Pancreatitissupporting
confidence: 81%
“…Dite et al [5] , in a prospective randomized trial comparing endoscopic and surgical therapy for chronic, painful, obstructive pancreatitis, reported complete resolution of pain at the five-year follow-up in 37% of patients after surgery and in 14% of those after endotherapy; short-term results were similar in the two groups. Similar data have been recently published by Cahen et al [6] .…”
Section: Chronic Pancreatitissupporting
confidence: 81%
“…Endoscopic therapy is recommended in symptomatic patients with benign pancreatic obstruction due to chronic pancreatitis or post-surgical stenosis [240,311,312]. Retrograde pancreatic stenting is technically successful in 85 -98 % of cases, with immediate clinical respite seen in 65 -95 % but lower pain relief on follow-up only in 32 -68 %.…”
Section: Eus-guided Pancreatography/drainage Backgroundmentioning
confidence: 99%
“…Retrograde pancreatic stenting is technically successful in 85 -98 % of cases, with immediate clinical respite seen in 65 -95 % but lower pain relief on follow-up only in 32 -68 %. Stenting can be used as a bridging procedure prior to surgical intervention, as surgery is superior to endoscopic treatment [122,311,312]. When ERP fails or surgical intervention is not feasible, alternative techniques are required.…”
Section: Eus-guided Pancreatography/drainage Backgroundmentioning
confidence: 99%
“…Few studies have compared endoscopic approaches with surgery. A recent randomized controlled Dutch trial compared endoscopic therapy with surgical drainage and suggested that surgical drainage was more effective in relieving obstruction and achieving pain relief [63]. However, most centres still attempt endoscopic therapy prior to surgery unless there is suspicion for pancreatic cancer possibly due to referral biases.…”
Section: Surgery Vs Endotherapymentioning
confidence: 99%